PENGGUNAAN METODE TECHNOLOGY ACCEPTANCE MODEL (TAM) DALAM PENGUKURAN PENERAPAN SISTEM INFORMASI PENERIMAAN MAHASISWA BARU DI UNIVERSITAS ‘AISYIYAH BANDUNG - Haris Hidayat (POLITEKNIK PIKSI GANESHA, 2022)
This study aims to measure the use of the New Student Admissions Information System for prospective new students online at 'Aisyiyah University Bandung in terms of the ease of access and information received by prospective new students. The measurement results will be used as a recommendation for the development and implementation of an online acceptance framework for prospective new students in the future. This research is a descriptive study with a total sample of 76 audiences obtained from the Bachelor of Nursing study program. The audience for this study were first-level students of the Bachelor of Nursing study program who used an online new student admission information system. The analysis technique uses quantitative analysis, namely the analysis of multiple regression methods, namely regression modeling or a kind of prediction that uses two independent variables (predictors) or more. The results of the study explain the magnitude of the correlation/relationship (R) value of 0.839. From this output, it is obtained a coefficient of determination (R Square) of 0.705 that the effect of the independent variable